My "r" Sound Box - Moncure, Jane Belk; Thornburgh, Rebecca McKillip (Mankato, MN Child's World, 2019)
"Little r has an adventure with items beginning with his letter's sound, such as a rooster, a raccoon, and a rowboat and raft on a rainy river."--Pprovided by publisher.
Keywords: Alphabet -- Juvenile fiction; Alphabet books; Alphabet; Rebuses; Readers (Primary)